Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Cách 1:
\(f\left(x\right)=\left(x^2-7x\right)\left(4x^3-2x^2-5x\right)=4x^5-30x^4+9x^3+35x^2\)
\(f'\left(x\right)=20x^4-120x^3+27x^2+70x\)
Cách 2:
\(f\left(x\right)=\left(x^2-7x\right)\left(4x^3-2x^2-5x\right)\)
\(f'\left(x\right)=\left(x^2-7x\right)'\left(4x^3-2x^2-5x\right)+\left(x^2-7x\right)\left(4x^3-2x^2-5x\right)'\)
\(f'\left(x\right)=\left(2x-7\right)\left(4x^3-2x^2-5x\right)+\left(x^2-7x\right)\left(12x^2-4x-5\right)\)
Bla bla.... Tự tách ra
\(f'\left(x\right)=20x^4-120x^3+27x^2+70\)
1) \(f\left(x\right)=2x-5\)
\(f'\left(x\right)=2\)
\(\Rightarrow f'\left(4\right)=2\)
2) \(y=x^2-3\sqrt[]{x}+\dfrac{1}{x}\)
\(\Rightarrow y'=2x-\dfrac{3}{2\sqrt[]{x}}-\dfrac{1}{x^2}\)
3) \(f\left(x\right)=\dfrac{x+9}{x+3}+4\sqrt[]{x}\)
\(\Rightarrow f'\left(x\right)=\dfrac{1.\left(x+3\right)-1.\left(x+9\right)}{\left(x-3\right)^2}+\dfrac{4}{2\sqrt[]{x}}\)
\(\Rightarrow f'\left(x\right)=\dfrac{x+3-x-9}{\left(x-3\right)^2}+\dfrac{2}{\sqrt[]{x}}\)
\(\Rightarrow f'\left(x\right)=\dfrac{12}{\left(x-3\right)^2}+\dfrac{2}{\sqrt[]{x}}\)
\(\Rightarrow f'\left(x\right)=2\left[\dfrac{6}{\left(x-3\right)^2}+\dfrac{1}{\sqrt[]{x}}\right]\)
\(\Rightarrow f'\left(1\right)=2\left[\dfrac{6}{\left(1-3\right)^2}+\dfrac{1}{\sqrt[]{1}}\right]=2\left(\dfrac{3}{2}+1\right)=2.\dfrac{5}{2}=5\)
a) = = .
b) = = .
c) = = .
d) y' =\(\dfrac{\left(x^2+7x+3\right)'\left(x^2-3x\right)-\left(x^2+7x+3\right)\left(x^2-3x\right)'}{\left(x^2-3x\right)^2}\)=\(\dfrac{\left(2x+7\right)\left(x^2-3x\right)-\left(x^2+7x+3\right)\left(2x-3\right)}{\left(x^2-3x\right)^2}\)=\(\dfrac{-2x^2-6x+9}{\left(x^2-3x\right)^2}\)
a: \(y'=4\cdot3x^2-3\cdot2x+2=12x^2-6x+2\)
b: \(y'=\dfrac{\left(x+1\right)'\left(x-1\right)-\left(x+1\right)\left(x-1\right)'}{\left(x-1\right)^2}=\dfrac{x-1-x-1}{\left(x-1\right)^2}=\dfrac{-2}{\left(x-1\right)^2}\)
c: \(y'=-2\cdot\left(\sqrt{x}\cdot x\right)'\)
\(=-2\cdot\left(\dfrac{x+x}{2\sqrt{x}}\right)=-2\cdot\dfrac{2x}{2\sqrt{x}}=-2\sqrt{x}\)
d: \(y'=\left(3sinx+4cosx-tanx\right)\)'
\(=3cosx-4sinx+\dfrac{1}{cos^2x}\)
e: \(y'=\left(4^x+2e^x\right)'\)
\(=4^x\cdot ln4+2\cdot e^x\)
f: \(y'=\left(x\cdot lnx\right)'=lnx+1\)
\(a,y'=8x^3-9x^2+10x\\ \Rightarrow y''=24x^2-18x+10\\ b,y'=\dfrac{2}{\left(3-x\right)^2}\\ \Rightarrow y''=\dfrac{4}{\left(3-x\right)^3}\)
\(c,y'=2cos2xcosx-sin2xsinx\\ \Rightarrow y''=-5sin\left(2x\right)cos\left(x\right)-4cos\left(2x\right)sin\left(x\right)\\ d,y'=-2e^{-2x+3}\\ \Rightarrow y''=4e^{-2x+3}\)
1) \(y=\dfrac{2x^2+1}{x^2}\)
\(\Rightarrow y'=\dfrac{\left(4x+1\right)x^2-2x\left(2x^2+1\right)}{x^4}\)
\(\Leftrightarrow y'=\dfrac{4x^3+x^2-4x^3-2x}{x^4}\)
\(\Leftrightarrow y'=\dfrac{x^2-2x}{x^4}=\dfrac{x\left(x-2\right)}{x^4}=\dfrac{x-2}{x^3}\)
2) \(f\left(x\right)=\sqrt[]{-5x^2+14x-9}\)
\(\Rightarrow f'\left(x\right)=\dfrac{-10x+14}{2\sqrt[]{-5x^2+14x-9}}\)
\(\Leftrightarrow f'\left(x\right)=\dfrac{-2\left(5x-7\right)}{2\sqrt[]{-5x^2+14x-9}}\)
\(\Leftrightarrow f'\left(x\right)=\dfrac{-\left(5x-7\right)}{\sqrt[]{-5x^2+14x-9}}\)
Để \(f'\left(x\right)=0\)
\(f'\left(x\right)=\dfrac{-\left(5x-7\right)}{\sqrt[]{-5x^2+14x-9}}=0\)
\(\Leftrightarrow5x-7=0\)
\(\Leftrightarrow5x=7\)
\(\Leftrightarrow x=\dfrac{7}{5}\)
Vậy tập hợp giá trị để \(f'\left(x\right)=0\) là \(\left\{\dfrac{7}{5}\right\}\)
1) \(y=x^2-3\sqrt[]{x}+\dfrac{1}{x}\)
\(\Rightarrow y=2x-\dfrac{3}{2\sqrt[]{x}}-\dfrac{1}{x^2}\)
2) \(f\left(x\right)=\dfrac{x+9}{x+3}+4\sqrt[]{x}\)
\(\Rightarrow f'\left(x\right)=\dfrac{1.\left(x+3\right)-1\left(x+9\right)}{\left(x+3\right)^2}+\dfrac{2}{\sqrt[]{x}}\)
\(\Rightarrow f'\left(x\right)=\dfrac{x+3-x-9}{\left(x+3\right)^2}+\dfrac{2}{\sqrt[]{x}}\)
\(\Rightarrow f'\left(x\right)=\dfrac{-6}{\left(x+3\right)^2}+\dfrac{2}{\sqrt[]{x}}\)
\(\Rightarrow f'\left(1\right)=\dfrac{-6}{\left(1+3\right)^2}+\dfrac{2}{\sqrt[]{1}}=-\dfrac{3}{8}+2=\dfrac{13}{8}\)
a: \(y'=\left(x^2+2x\right)'\left(x^3-3x\right)+\left(x^2+2x\right)\left(x^3-3x\right)'\)
\(=\left(2x+2\right)\left(x^3-3x\right)+\left(x^2+2x\right)\left(3x^2-3\right)\)
\(=2x^4-6x^2+2x^3-6x+3x^4-3x^2+6x^3-6x\)
\(=5x^4+8x^3-9x^2-12x\)
b: y=1/-2x+5
=>\(y'=\dfrac{2}{\left(2x+5\right)^2}\)
c: \(y'=\dfrac{\left(4x+5\right)'}{2\sqrt{4x+5}}=\dfrac{4}{2\sqrt{4x+5}}=\dfrac{2}{\sqrt{4x+5}}\)
d: \(y'=\left(sinx\right)'\cdot cosx+\left(sinx\right)\cdot\left(cosx\right)'\)
\(=cos^2x-sin^2x=cos2x\)
e: \(y=x\cdot e^x\)
=>\(y'=e^x+x\cdot e^x\)
f: \(y=ln^2x\)
=>\(y'=\dfrac{\left(-1\right)}{x^2}=-\dfrac{1}{x^2}\)